How realistic is Belt and Road Initiative for Kyrgyzstan and Central Asian Countries? - Akmoldoev, Kiyalbek ([OrdnungsPolitisches Portal], 2022)
Due to the geographical location of the Central Asian countries and Kyrgyzstan, which do not have direct access to the sea, there is a dependence on the transport route via Kazakhstan, Russia, and Belarus to trade goods with the European market. The Chinese BRI project would offer an alternative for Central Asian countries to connect economically with European, Middle Eastern and West Asian countries. However, turning away from Russia and toward China holds potential for conflict. Therefore, the main objective of this article is to analyze the BRI projects in Central Asia and predict how realistic it is to implement them without the
10419/265258
Keywords: Graue Literatur; Belt and Road Initiative; Kyrgyzstan; Geopolitics; Debt-Trap; Silk Road Route